Adsorption of Petroleum Fractions on Organo-Modified Calcium Bentonite (International Journal of Scientific Research and Management (IJSRM), 2020)
This work aims to obtain an organoclay from a local Nigerian bentonite with Cetyl trimetyl-Ammonium bromide (CTAB), a quaternary ammonium compound which possesses surfactant properties. The studied natural bentonite (calcium bentonite) was obtained from Anambra state and modified with CTAB via impregnation techniques. Modification was achieved by varying the concentration of the modifier from 0.02 - 0.15mol/L. Adsorption test was carried out using Water, Petrol (PMS), Kerosene (DPK) and Automotive Gas Oil (AGO) on both modified and unmodified bentonite. The result showed that unmodified bentonite adsorbed more water than hydrocarbons while Modified bentonite adsorbed more hydrocarbons than water. The result also shows that the amount of each hydrocarbon adsorbed increases with an increase in the concentration of the modifier with a subsequent decrease in the amount of water adsorbed. This indicates that the modified bentonite was now organophilic. Therefore, this research shows that the bentonite modified with CTAB can be used in oil spill remediation and also to mop up hydrocarbons from the Environment.